Kinetics of stop-flow atomic layer deposition for high aspect ratio template filling through photonic band gap measurements - Karuturi, Siva Krishna (2011)
Atomic layer deposition (ALD) is shown as a unique method to produce high aspect ratio (AR) nanostructures through conformal filling and replication of high AR templates. The stop-flow process is often used as an alternative to the conventional continuous flow process to obtain high step coverage. However, there is a need for understanding the deposition kinetics and optimizing the deposition process to fabricate defect-free nanostructures. In this Article, TiO2 ALD in high AR self-assembled opal photonic crystal templates was performed in stop-flow fill−hold−purge process in comparison with continuous flow pulse−purge process. Photonic band gap properties of opal templates were characterized and compared with simulated band diagrams for quantitative investigation of filling kinetics and the effect of shrinking pore size on filling uniformity. Γ−L bands in the transmittance spectra of ALD-infiltrated opals accurately represented the depth profile of the depositions without the need for expensive sample preparation techniques and characterization tools. It was found that the stop-flow process attains higher Knudsen flow rates of precursor gases, thereby achieving homogeneous and complete filling at considerably lower cycle time.